PERSONNEL POLICY OF THE SUPREME AUTHORITIES OF NAKHCHIVAN: REPRESSION IN NAKHCHIVAN: DEPORTATION OF THE POPULATION OF NAKHCHIVAN (1924–1930) - Yegana Mammadova (International Journal of Innovative Technologies in Social Science, 2026)
As in all parts of Azerbaijan, repression, genocide, and deportation were carried out with particular brutality in Nakhchivan throughout all periods, and they continued at the same level during the time when the Nakhchivan ASSR was established. In general, the Soviet era can be described as a major tragic period for the country, and historical sources confirm the bitter consequences of this tragedy in the Nakhchivan ASSR as well, including repression, genocide, and deportation. At the same time, it should be noted that the deportations, genocides, and repressions that spanned centuries cannot be confined solely to the most severe period of history—the 1920s–1930s. Essentially, deportation was also one form of Russian-Armenian aggression against Azerbaijan. Therefore, the repressions carried out in Nakhchivan during 1924–1930 were simultaneously accompanied by acts of deportation. Historical sources clearly demonstrate this. From this perspective, there is a significant need in historiography for a comprehensive study of the deportations of these years.